Determination of Benzyl-hexadecyldimethylammonium 1,4-Bis(2-ethylhexyl)sulfosuccinate vesicle permeability by using square wave voltammetry and an enzymatic reaction - Cobo Solis, Airam Katiza (2017)
This report describes the studies performed to determine the permeability coefficient value (P) of 1-naphthyl phosphate (1-NP) through the benzyl-hexadecyldimethylammonium 1,4-bis(2-ethylhexyl)sulfosuccinate (AOT-BHD) vesicle bilayer. 1-NP was added in the external phase and must cross the bilayer of the vesicle to react with the encapsulated enzyme (alkaline phosphatase) to yield 1-naphtholate (NPh-), the product of the enzymatic hydrolysis. This product is electrochemically detected, at basic pH value, by a square wave voltammetry technique, which can be a good alternative over the spectroscopic one, to measure the vesicle solutions because scattering (due to its turbidity) does not make any influence in the electrochemical signal. The experimental data allow us to propose a mathematical model, and a value of P = (1.00 ± 0.15) × 10-9 cm s-1 was obtained. Also, a value of P = (2.0 ± 0.5) × 10-9 cm s-1 was found by using an independent technique, ultraviolet-visible spectroscopy, for comparison. It is evident that the P values obtained from both the techniques are comparable (within the experimental error of both techniques) under the same experimental conditions. This study constitutes the first report of the 1-NP permeability determination in this new vesicle. We want to highlight the importance of the introduction of a new method and the electrochemical response of the product generated through an enzymatic reaction that occurs in the inner aqueous phase of the vesicle, where the enzyme is placed.